Targeting ROR1 inhibits the self‐renewal and invasive ability of glioblastoma stem cells. (28th February 2016) - Jung, Eun‐Hwa; Lee, Han‐Na; Han, Gi‐Yeon; Kim, Min‐Jung; Kim, Chan‐Wha
Abstract : Glioblastoma is the most malignant of brain tumours and is difficult to cure because of interruption of drug delivery by the blood–brain barrier system, its high metastatic capacity and the existence of cancer stem cells (CSCs). Although CSCs are present as a small population in malignant tumours, CSCs have been studied as they are responsible for causing recurrence, metastasis and resistance to chemotherapy and radiotherapy for cancer. CSCs have self‐renewal characteristics like normal stem cells. The aim of this study was to investigate whether receptor tyrosine kinase‐like orphan receptor 1 (ROR1) is involved in stem cell maintenance and malignant properties in human glioblastoma. Knockdown of ROR1 caused reduction of stemness and sphere formation capacity. Moreover, down‐regulation of ROR1 suppressed the expression of epithelial‐mesenchymal transition‐related genes and the tumour migratory and invasive abilities. The results of this study indicate that targeting ROR1 can induce differentiation of CSCs and inhibit metastasis in glioblastoma. In addition, ROR1 may be used as a potential marker for glioblastoma stem cells as well as a potential target for glioblastoma stem cell therapy. Copyright © 2016 John Wiley & Sons, Ltd.